Mycoplasma genitalium prevalence, antimicrobial resistance-associated mutations, and coinfections with non-viral sexually transmitted infections in high-risk populations in Guatemala, Malta, Morocco, Peru and South Africa, 2019–2021 - Shipitsyna, Elena; Kularatne, Ranmini; Golparian, Daniel; Müller, Etienne E.; Vargas, Silver K.; Hadad, Ronza; Padovese, Valeska; Hancali, Amina; Alvarez, Christian S.; Oumzil, Hicham; Camey, Elsy; Blondeel, Karel; et al. (Frontiers in Microbiology, 2023)
The prevalence of Mycoplasma genitalium (MG) and MG antimicrobial resistance (AMR) appear to be high internationally, however, prevalence data remain lacking globally. We evaluated the prevalence of MG and MG AMR-associated mutations in men who have sex with men (MSM) in Malta and Peru and women at-risk for sexually transmitted infections in Guatemala, South Africa, and Morocco; five countries in four WHO regions mostly lacking MG prevalence and AMR data, and estimated MG coinfections with Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Trichomonas vaginalis (TV). Male urine and anorectal samples, and vaginal samples were tested for MG, CT, NG, and TV (only vaginal samples) using Aptima assays (Hologic). AMR-associated mutations in the MG 23S rRNA gene and parC gene were identified using ResistancePlus MG kit (SpeeDx) or Sanger sequencing. In total, 1425 MSM and 1398 women at-risk were recruited. MG was detected in 14.7% of MSM (10.0% in Malta and 20.0% Peru) and in 19.1% of women at-risk (12.4% in Guatemala, 16.0% Morocco, 22.1% South Africa). The prevalence of 23S rRNA and parC mutations among MSM was 68.1% and 29.0% (Malta), and 65.9% and 5.6% (Peru), respectively. Among women at-risk, 23S rRNA and parC mutations were revealed in 4.8% and 0% (Guatemala), 11.6% and 6.7% (Morocco), and 2.4% and 3.7% (South Africa), respectively. CT was the most frequent single coinfection with MG (in 2.6% of MSM and 4.5% of women at-risk), compared to NG+MG found in 1.3% and 1.0%, respectively, and TV+MG detected in 2.8% of women at-risk. In conclusion, MG is prevalent worldwide and enhanced aetiological MG diagnosis, linked to clinical routine detection of 23S rRNA mutations, in symptomatic patients should be implemented, where feasible. Surveillance of MG AMR and treatment outcome would be exceedingly valuable, nationally and internationally. High levels of AMR in MSM support avoiding screening for and treatment of MG in asymptomatic MSM and general population. Ultimately, novel therapeutic antimicrobials and/or strategies, such as resistance-guided sequential therapy, and ideally an effective MG vaccine are essential.